Abnormal regulation of the oestrogen receptor in benign breast lesions. Issue 10 (1st October 2000) - Shoker, B S; Jarvis, C; Clarke, R B; Anderson, E; Munro, C; Davies, M P A; Sibson, D R; Sloane, J P
Abstract : Background —In normal breast tissue the oestrogen receptor (ER) and the proliferation associated antigen Ki67 are negatively associated, indicating that ER+ cells are non-dividing, or that the receptor is downregulated as cells enter cycle. This relation is completely or partially lost in many ER+ breast cancers and in in situ proliferations associated with an increased cancer risk, where coexpression of the two markers is often found. Aims —To determine whether similar changes can be identified in other risk associated breast lesions. Patients/Methods —Paraffin wax blocks from 12 cases of lactational change, 21 apocrine metaplasias, 22 duct ectasias, 20 sclerosing adenosis, 20 fibroadenomas, 19 phyllodes tumours, 20 radial scars, 21 papillomas (15 solitary and six multiple), 15 gynaecomastias, and nine postmortem male breast tissues were retrieved. Immunohistochemistry was used to determine the expression of ER and dual labelling immunofluorescence was used to detect cells expressing both ER and Ki67. Results —Increased numbers of ER+ cells were seen in sclerosing adenosis, radial scars, papillomas, fibroadenomas, and phyllodes tumours but not in apocrine cysts (where no ER+ cells were detected) or duct ectasia (where normal numbers were found). As in the normal breast, the proportion of ER+ cells increased with age in all lesions with the exception of fibroadenomas. Coexpression of ER and Ki67 was found in an increased proportion of cells of all risk associated lesions studied. ER+ cells were less likely to be dividing than ER− cells in all cases, although this was significant only for sclerosing adenosis. The data on sclerosing adenosis, radial scars, papillomas, and fibroadenomas are comparable with those reported previously in hyperplasia of usual type, whereas those in duct ectasia are similar to those of the normal breast. The findings in all lesions, however, differed from those in ductal carcinoma in situ, where proportions of ER+ and ER+/Ki67+ cells are higher and the relation between ER+ cell numbers and age is lost. Thus, the nature and degree of dysregulation of ER in benign breast lesions is broadly in accordance with the degree of risk of developing breast cancer with which they are associated. In gynaecomastia, the proportions of ER+ and ER+/Ki67+ cells were comparable with those seen in benign female breast lesions, but changes with age were not observed. However, the changes in gynaecomastia were similar to those seen in normal male breast. Conclusion —These findings are in keeping with the contention that the dissociation of ER and Ki67 expression is a very early change in the pathway to many breast cancers. However, this change might only have preneoplastic importance in the hormonal milieu of the female breast.